Fostering Higher Order Thinking Skills in Mathematics Learning: A Scoping Review of Teacher Development Initiatives - Ega Gradini; Ali Umar; Firmansyah Firmansyah; Yusuf Effendi; Winardi Winardi (Pascasarjana Universitas Mataram, 2024)
This community service program aimed to enhance both the understanding and application of Higher-Order Thinking Skills (HOTs) in mathematics instruction for participating teachers. Employing a targeted professional development approach informed by the Community-Based Participatory Research (CBPR) framework, the program equipped 21 mathematics teachers from Musyawarah Guru Mata Pelajaran (MGMP) in Aceh Tengah District, Indonesia, with the necessary knowledge and pedagogical strategies to foster and cultivate high-level thinking skills in their students. The program demonstrably improved teachers' knowledge, skills, and commitment towards implementing HOTs-oriented instruction. While areas like solving HOTs questions necessitate further attention, the overall results suggest success, paving the way for continued advancements in promoting deep-thinking and problem-solving skills in mathematics education. Analysis of the data reveals a positive impact of the program on teachers' understanding of HOTs. While areas such as problem-solving and critical thinking require further development, the program evidently achieved its goals of raising awareness, knowledge, and application skills related to HOTs. Building upon this foundation, future interventions can delve deeper into these advanced skills, further empowering teachers to cultivate critical thinking and problem-solving abilities in their students.